Pengaruh Debt to Equity Ratio (DER), Growth Dan Dividen Terhadap Nilai Perusahaan Pada Perusahaan Sektor Pertambangan - Riski Wijayanti; Agtovia Frimayasa; Fathihani (CV ODIS, 2023)
This study analyses the influence of Debt to Equity Ratio (DER), Growth, and Dividends on Firm Value in the mining sector. The data used in this research are secondary data from mining companies listed on the Indonesia Stock Exchange. The results of multiple regression analysis show that the Growth variable significantly influences Firm Value. In contrast, the Debt to Equity Ratio (DER) and Dividend variables are insignificant. The implications of this study highlight the importance of focusing on company growth to enhance Firm Value, as well as paying attention to financial health and appropriate capital structure